Stress behaviour of surface-coated materials in concentrated sliding contact - 안효석; B. J. Roylance (ELSEVIER SCIENCE, 1990)
The stress behaviour at the surface and in the near-surface region of layered (surface-coated) solids in concentrated sliding contact is investigated using the finite element method. Of particular interest is the behaviour of an elastic layer on an elastic substrate normally loaded by an elastic indenter and taking account of tangential loading at the interface. Stress contour plots are generated for "hard" and "soft" layers when expressed in terms of von Mises' shear strain energy criterion normalized with respect to the maximum Hertz stress. The consequences of varying parameters such as friction coefficient, elastic modulus and layer thickness are examined. ？ 1990.